Observation of $Z$ production in proton-lead collisions at LHCb - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Akar, S; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (Springer Verlag, 2014)
The first observation of $Z$ boson production in proton-lead collisions at a centre-of-mass energy per proton-nucleon pair of $\sqrt{s_{NN}}=5~\text{TeV}$ is presented. The data sample corresponds to an integrated luminosity of $1.6~\text{nb}^{-1}$ collected with the LHCb detector. The $Z$ candidates are reconstructed from pairs of oppositely charged muons with pseudorapidities between 2.0 and 4.5 and transverse momenta above $20~\text{GeV}/c$. The invariant dimuon mass is restricted to the range $60-120~\text{GeV}/c^2$. The $Z$ production cross-section is measured to be \begin{eqnarray*} σ_{Z→μ^+μ^-}(\text{fwd})and=and13.5^{+5.4}_{-4.0}\text{(stat.)}±1.2\text{(syst.)}~\text{nb} \end{eqnarray*} in the direction of the proton beam and \begin{eqnarray*} σ_{Z→μ^+μ^-}(\text{bwd}) and =and10.7^{+8.4}_{-5.1}\text{(stat.)}±1.0\text{(syst.)}~\text{nb} \end{eqnarray*} in the direction of the lead beam, where the first uncertainty is statistical and the second systematic.